Pedestal platform for low loss doped amplifiers and nonlinear optics - Carvalho, Daniel O. [UNESP]; Kassab, Luciana R.P. [UNESP]; Alayo, Marco I. (Institute of Electrical and Electronics Engineers (IEEE), 2017)
In this work we review and summarize the recent developments regarding pedestal waveguide fabrication technology and demonstrate the applicability of this type of structure for Nonlinear Optics (NLO) integrated devices. Pedestals show great potential as a platform for exploring new optical materials. The fabrication process of this type of waveguide does not require etching of the core material itself, making it possible to explore materials that are highly inert to chemical etchants or alloys composed of heavy metal elements, which would not be usually suitable for this purpose otherwise. Lower propagation losses can be achieved with pedestal waveguide when compared to rib waveguides fabricated with different materials. Since the pedestal process allows the exploitation of novel materials, optical amplifiers with higher gain have been demonstrated using this procedure. We show that pedestals could also greatly benefit the field of nonlinear optics, where novel materials with high nonlinearities could be explored as well.
Keywords: Doped Amplifiers; integrated photonics; Nonlinear Optics; novel material platforms; Pedestal waveguides